Using Vocabulary Self-Collection Strategy (VSS) to Improve Mastery Student’s Vocabulary - Putri Anita Simbolon; Feber Anggelina Br Bangun; Sumianti Magdalena Pardede; Jelinta Br Tarigan; Sri Ninta Br Tarigan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The research aims to know that Vocabulary Self-collection Strategy (VSS) can improve students’ vocabulary mastery and to find out how far Vocabulary Self-Collection Strategy (VSS) can be useful for the students' vocabulary mastery at the second-grade students of SMP Sinar Husni Medan. The methodology of this research used Classroom Action Research. It was conducted on a two-cycle. In analyzing the data, the researcher used quantitative data. The implementation of Vocabulary Self-collection Strategy (VSS) in teaching vocabulary at eight grade students was successful. It can be seen from the progress of the mean score in cycle I to cycle II. Mean score in a period I 71.20 % and rating in cycle II 78.80 %. The implementation Vocabulary Self-collection Strategy (VSS) as a learning strategy was not only increasing students' mean score but also increase students' motivation and behavior. The students were more interested, happy, and active in teaching-learning English, especially vocabulary. Based on the result above, it could be concluded that Vocabulary Self - Collection Strategy (VSS) improved their students’ vocabulary mastery. Keywords: vocabulary mastery, vocabulary self-collection strategy (VSS)